Implementation of the Law on the Validity of Electronic Cetificates as Ownership of Land Rights in Indonesia - Hermawan, Agus; Pribadi, Devi Wahyu; Alfiana, Sheyla Alif; Ellena, Tania (Journal of Law, Politic and Humanities, 2025)
The Indonesian government, through the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN), has begun implementing an electronic certificate policy as part of the digital transformation of the national land system. The purpose of the study is to analyze, identify and recommend legal implementation to improve the protection of the rights of electronic certificate land owners. The research method uses a qualitative method with a normative legal research type with a statutory and conceptual approach. The results of the study show that electronic certificates have valid legal force based on the Regulation of the Minister of ATR/BPN Number 1 of 2021 and the Law on Information and Electronic Transactions. Although it has a strong legal basis, its implementation still faces challenges in the form of limited digital infrastructure, low public literacy, and concerns about data security. Therefore, it is necessary to strengthen the legal protection system and comprehensive socialization to the community. In conclusion, the legal validity of electronic certificates is not only determined by the normative framework, but is also supported by public trust, the integrity of the digital system, and legal protection that is equivalent to physical certificates. Research Strengthening technological infrastructure, digital literacy, and a reliable monitoring system are the keys to success.